Basal cell adenoma with S100 protein–positive “stroma”: a distinct triphasic salivary gland neoplasm characterized by CTNNB1 mutation - Skálová, Alena; Bradová, Martina; Laco, Jan; Vaněček, Tomáš; Hájková, Veronika; Martínek, Petr; Grendár, Marián; Querzoli, Giulia; Leivo, Ilmo; Michal, Michal (Springer Science and Business Media LLC, 2025)
Basal cell adenoma (BCA) is a benign salivary neoplasm that exhibits a divergent spectrum of growth patterns, including cribriform, tubular, trabecular, membranous, and solid. A subset of BCAs is characterized by the presence of abundant S100 protein–positive stroma, which makes this variant unique and potentially represents a hybrid lesion or an entity intermediate between BCA and pleomorphic adenoma (PA). From the authors’ registry, we selected 17 cases of BCA with abundant S100 protein–positive stromal components and compared them with 7 cases of BCA without S100 protein–positive stroma, and 6 cases of myoepithelial cell–rich PAs. All cases were analyzed by immunohistochemistry (IHC) using antibodies to S100 protein, SOX10, PLAG1, HMGA2, p63/p40, cytokeratins, EMA, LEF1, and/or β-catenin. Next-generation sequencing (NGS), fluorescence in situ hybridization (FISH) for the rearrangement of PLAG1, and methylation analysis were performed. The BCA S100 protein stromal cell–rich group consisted of 7 males and 10 females with an average age of 62 years. Their tumors showed typical S100 protein–positive stroma, which was also positive for SOX10 in all cases. The stromal and/or epithelial components showed expression of LEF1 and β-catenin in 17 and 15 cases, respectively. HMGA2 IHC showed nuclear expression in one case while PLAG1 was negative in all cases. In 11 cases, one or more mutations were present, including CTNNB1 mutation (n = 11). The first control cohort of BCA without S100 protein–positive stroma consisted of 1 male and 6 females with an average age of 50 years. This group showed LEF1 and nuclear β-catenin expression in 1 and 2 cases, respectively. The second control group of PA (including 4 spindle-shaped cellular and 2 oncocytic PAs) was devoid of CTNNB1 mutations. Two cases presented with gene fusions, including MEG3::PLAG1 and ACTA2::PLAG1, and an additional two cases showed PLAG1 break. It has been proposed earlier that BCA is related to PA based on a shared biphasic nature and a divergent spectrum of growth patterns. Our findings suggest that BCAs with abundant S100 protein–positive stroma are tumors that morphologically display tricellular differentiation into inner (luminal) ductal epithelial cells, outer (abluminal) basaloid myoepithelial cells, and spindle-shaped stromal S100-positive cells (stromal abluminal). According to our investigation, BCAs with S100 protein–positive stroma represent a distinctive triphasic subset of BCA, which is substantially different from PA, both in immunoprofile and molecular underpinnings.